The stick and carrot approach to moneylendersâ self-regulation in Klang Valley, Malaysia - Sandhu, Daljit Kaur; Muhammad Arif, Afida Mastura; Abu Bakar, Elistina; Abd Rahim, Husniyah (Universiti Putra Malaysia, 2021)
The vital role played by the moneylending industry in Malaysia resulted in 1,496 licensed moneylenders registered within the Klang Valley, in 2020. Even though the Moneylenders Act 1951 exist to protect the industry, law enforcement is a challenge to the regulator. This is evident as many borrowers’ complaints were made towards the moneylenders on poor self-regulation and questionable business practices. In understanding this gap, the main research objective is to gain insights on licensed moneylenders self-regulation in the moneylending process involving the borrowers. The Interpretative Phenomenology Analysis approach was used in extracting four themes from the twelve licensed moneylenders’ experiences. It was discovered that many of the moneylenders lacked the understanding of their rights and duties as stipulated in the Act. The apprehension of selfregulation amongst the licensed moneylenders was gravely misleading and require the regulator’s re-educational intervention. The first implication of the study is for the moneylenders and associations representing them. They must take remedial action to educate members on the value of practising business ethics in closing on the disparity found in their self-regulation throughout the moneylending process. The second implication is for the regulator to assess moneylenders practical adherence when introducing new business requirements.